Awaking Blood Pressure Surge and Progression to Microalbuminuria in Type 2 Normotensive Diabetic Patients. (28th December 2015) - Barbieri, Michelangela; Rizzo, Maria Rosaria; Fava, Ilaria; Sardu, Celestino; Angelico, Nicola; Paolisso, Pasquale; Abbatecola, Angela; Paolisso, Giuseppe; Marfella, Raffaele
Abstract : Background . We investigated the predictive value of morning blood pressure surge (MBPS) on the development of microalbuminuria in normotensive adults with a recent diagnosis of type 2 diabetes. Methods . Prospective assessments of 24-hour ambulatory blood pressure monitoring and urinary albumin excretion were performed in 377 adult patients. Multivariate-adjusted Cox regression models were used to assess hazard ratios (HRs) between baseline and changes over follow-up in MBPS and the risk of microalbuminuria. The MBPS was calculated as follows: mean systolic BP during the 2 hours after awakening minus mean systolic BP during the 1 hour that included the lowest sleep BP. Results . After a mean follow-up of 6.5 years, microalbuminuria developed in 102 patients. An increase in MBPB during follow-up was associated with an increased risk of microalbuminuria. Compared to individuals in the lowest tertile (−0.67 ± 1.10  mmHg), the HR and 95% CI for microalbuminuria in those in the highest tertile of change (24.86 ± 6.92  mmHg) during follow-up were 17.41 (95% CI 6.26–48.42); p for trend <0.001. Mean SD MBPS significantly increased in those who developed microalbuminuria from a mean [SD] of 10.6 [ 1.4 ] to 36.8 [ 7.1 ], p < 0.001 . Conclusion . An increase in MBPS is associated with the risk of microalbuminuria in normotensive adult patients with type 2 diabetes.